Cloud Environment Workload Prediction - Krishnan, Smitha; Prashanthi, .B.G (International Journal of Psychosocial Rehabilitation, 2019)
Scalability and elasticity are very important features in Cloud environment. Analysis of workload can be done and future work load can be predicted for better resource allocation and efficacy of cloud platform there by reducing the cost. A number of regression models are taken for that.